Characterization morfology of Nepenthes spp. in the lowlands XIII Koto Kampar District, Riau - Azhar, Syaiful; Tambunan, Muhammad Iqbal H.; Adlini, Miza Nina; Sirait, Fitriatul Aspahani (Univeritas Papua, 2025)
Lowlands such as peat swamps have specific, limited conditions that play a role in storing the world's main carbon, one of the plants that adapts is Nepenthes. This is important considering that peatlands in Indonesia face the threat of deforestation, while Nepenthes is a protected plant. So it is important to know the type and characteristics of Nepenthes in that location. Kampar Regency is an undulating area with lowland swamps. The research was conducted in August 2023, using a purposive sampling exploration method at locations considered to have potential. The samples found were recorded for habitat characteristics (altitude, temperature and coordinates) and photographed and collected (herbarium) for observation of their morphological characteristics. The results of the study found 3 types, namely N. gracilis, N. ampullaria, N. mirabilis, classified as lowland Nepenthes. The Nepenthes found were at 94-131 meters above sea level with a temperature range of 27-33 C. The morphological characteristics of Nepenthes are generally the same as similar characters in other areas. There are concerns about ecological disruption to the remaining lowland Nepenthes habitat in Koto Kampar. Therefore, this research is expected to be complementary data on biodiversity information in Riau, especially in the lowlands of Koto Kampar District.